SISTEM INFORMASI INVENTORY BARANG MENGGUNAKAN METODE FIRST-IN FIRST-OUT (FIFO) BERBASIS WEB (STUDI KASUS PT. RIYANA CIPTA PANGAN INDONESIA) (INTI TALAFA, 2023)
PT. Riyana Cipta Pangan is a company operating in the manufacturing sector which is engaged in the production of pastries and drinks. PT. Riyana Cipta Pangan already has an Inventory where raw materials, semi-finished goods and finished goods are stored. Inventory management is very important to increase the company's productivity and performance in managing goods and stock. Currently the inventory that is running is still manual and has many weaknesses and deficiencies, causing the company's performance to be hampered and unable to support all the company's desired needs, such as the noble process from recording goods to compiling reports which takes time. This research aims to analyze and design a web-based inventory information system needed by companies. The Performance, Information, Economy, Control, Efficiency, and Service (PIECES) analysis method is used to assist the ongoing system analysis process. Designing and designing a goods inventory information system using the Rapid Application Development (RAD) method as a system development method and Unified Modeling Language (UML) as a modeling tool. The operations designed in this system consist of goods management, customer management, supplier management, incoming goods management, outgoing goods management, goods requests, inventory management, user management, and reports. The First-In First-Out (FIFO) inventory valuation method is applied to the process of placing and returning goods to simplify the activities of getting goods in and out. From this research, a web application for the PT Riyana Cipta Pangan Goods Inventory Information System was produced, which is one of the solutions to the company's problems. Keywords: Inventory System, Unified Modeling Language (UML), First-In First-Out (FIFO).